Gas-Phase Conversion of 1,3-Dithiolane-2-Thione Into 1,3-Dithiolan-2-One Over Molybdenum Trioxide - Aitken, R. Alan; Curzon, Thomasine E.; Andrews, Matthew J. (Frontiers in Chemistry, 2019)
Gas-phase reaction of 1,3-dithiolane-2-thione over molybdenum trioxide supported on pumice stone results in efficient conversion into 1,3-dithiolan-2-one. The solid reagent is regenerated on exposure to air and thus acts as a catalyst for the overall conversion of the thione and oxygen from the air into the ketone and sulfur dioxide. The process can be carried out under either dynamic vacuum or atmospheric pressure flow conditions and using a catalyst prepared either by physical mixing of MoO3 with the support or by solution impregnation, with an isolated yield of up to 67% obtained.